Kontribusi Pendapatan Usahatani Padi Sawah Terhadap Pendapatan Petani di Kecamatan Maro Sebo Kabupaten Muaro Jambi - Yuni Sarah Sihombing; Suandi Suandi; Ardhiyan Saputra (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2024)
Increasing Rice is a crucial food crop that significantly contributes to the food security of farming households. This study aims to determine farmers' income from rice farming in Maro Sebo District, Muaro Jambi Regency. Additionally, it seeks to determine the income generated from other farming enterprises outside of rice farming in the same district. The research assesses the contribution of rice farming income to farmers' overall income in Maro Sebo District, Muaro Jambi Regency. Conducted between June and July 2024, this research focuses on rice farmers in the area. The observed variables include rice farming and other agricultural businesses, such as oil palm and rubber farming, as well as non-agricultural activities or labor. Data sources consist of both secondary data and primary data collected through questionnaires. A simple random sampling technique resulted in 42 rice farmer samples. The analysis method used is descriptive. The findings reveal that the income from rice farming is the lowest compared to other agricultural activities. Oil palm farming represents the highest income, followed by rubber farming. The lowest income is derived from non-agricultural work (labor). The analysis results show that rice farming income contributes only 4.54 percent to the total income of farmers in Maro Sebo District, Muaro Jambi Regency.